List of reviewers - Editorial Team (Ordines Militares Colloquia Torunensia Historica. Yearbook for the Study of the Military Orders, 2023)
Attila Bárány, Történettudományi Intézet, Debreceni Egyetem Nicholas Coureas, Cyprus Research Centre / Kentro Epistemonikon Ereunon, Nicosia Maciej Dorna, Instytut Historii, Uniwersytet im. Adama Mickiewicza w Poznaniu Peter Edbury, Emeritus, School of History, Archaeology and Religion, Cardiff University Anton Caruana Galizia, School of Historical Studies, Newcastle University Cordelia Heß, Historisches Institut, Universität Greifswald Carsten Jahnke, Saxo-Instituttet, Københavns Universitet Waldemar Könighaus, Akademie der Wissenschaften zu Göttingen Ilgvars Misāns, Vēstures un filozofijas fakultāte, Latvijas Universitāte, Rīga Johannes A. Mol, Emeritus, Instituut voor Geschiedenis, Universitaet Leiden Nicholas Morton, School of Arts & Humanities, Nottingham Trent University Piotr Oliński, Instytut Historii i Archiwistyki, Uniwersytet Mikołaja Kopernika w Toruniu László Pósán, Történettudományi Intézet, Debreceni Egyetem Anti Selart, Ajaloo ja arheoloogia instituut, Tartu Ülikool Marek Smoliński, Instytut Historii, Uniwersytet Gdański Janusz Tandecki, Emeritus, Instytut Historii i Archiwistyki, Uniwersytet Mikołaja Kopernika w Toruniu Ewald Volgger, Institut für Liturgiewissenschaft und Sakramententheologie, Katholische Privat-Universität Linz